Humanist Literacy Links in Critical Reading: Future Learning Directions - Asnawi Asnawi; Ida Zulaeha; R. M Teguh Supriyanto; Hari Bakti Mardikantoro; Sri Wahyuni (International Conference on Science, Education, and Technology, 2021)
Critical reading is a very necessary competency in the millennial era. Readers are required to think and reason critically to selectively accept the information obtained. Therefore, as a reader, you must be able to filter information that is in accordance with the characteristics of the Indonesian people based on Pancasila. This is in accordance with the demands of future learning to make Pancasila students. Critical reading strands humanist literacy, one way that can be done to form a profile of Pancasila students. Humanist literacy is an activity that aims to communicate and collaborate on human attitudes. The purpose of this study is to find the characteristics of critical reading learning materials that link humanist literacy as a future learning direction. The data of this research are in the form of questionnaires and interview results from 16 lecturers spread across four major universities in Riau. The method of data collection was done through observation, questionnaires, and interviews. The data analysis technique was carried out reflectively with the help of TagCrowd and AntConc. Based on the results of the study, it was found that the characteristics of the desired critical reading learning material include, (1) the material is oriented towards humanist literacy activities, (2) uses the Malay Teaching Text, (3) is oriented to the attitude and behavior approach (psychodidactic), (4) presents the critical reading content of the Tunjuk Ajar Melayu text links humanist literacy, (5) has material that is in accordance with the characteristics of Malay culture.